Feasibility Analysis of Layer Chicken Darwis Farm Business in Lintau Buo District - Juli Supriyanti (Jurnal Serambi Biologi, 2021)
This study aims to determine: (i) the production costs and income of laying hens at Darwis Farm in Lintau Buo District, Tanah Datar District. (ii) the feasibility of laying hens at Darwis Farm in Lintau Buo District. This research was conducted in January-August 2020. The method used was the case study method. The research location was chosen purposively in the Lintau Buo sub-district, Tanah Datar Regency in the Darwis Farm Laying Chicken Farming Business. Data collection techniques with interviews and surveys. The data analysis method used is descriptive qualitative and quantitative analysis. From the results of the study it was found that laying hen farming techniques consisted of several stages, namely the provision of DOC, the production process, feeding, cleaning the cage, administering vaccines, administering drugs and multivitamins. The production costs for the Darwis Farm Laying Chicken business are Rp. 1,479,048,131, revenues are Rp. 3,396,800, revenues are Rp. 1,995,753,329. R/C ratio of 2.2. This shows that this livestock business is profitable, because the R/C ratio is > 1, this business is feasible to be cultivated